Study on Biomedical Waste Management in Surgical Theaters of Some Selected Hospitals in Urban Kano, Northern Nigeria - Sani, M.; Imam, T.S.; Nahannu, M.S.; Gwarzo, F.S. (International Journal of Scientific Research in Biological Sciences, 2021)
Biomedical waste management (BMW) is one very important aspect of environmental issue that needs to be taken more seriously. Rapid growth of human population especially in the developing countries has led to increase in quantity of biomedical waste produced in the health care facilities (HCF). The paper aimed at studying management of MW in surgical theaters in Urban Kano. A total of twelve (12) of HCFs were purposively sampled base on possession of a functioning theater, from the six major local government areas constituting urban Kano (one public and the other private). Questionnaire survey was used to solicit information from the theater attendants on various aspects of waste management: waste segregation, collection, storage, treatment, transportation, disposal, safety and exposure to risk as well as training. Out of 105 questionnaires administered, 81 representing 77% were retrieved. It was found out that waste segregation is poorly practiced, (26%), waste is poorly stored, treatment also very low, reported by only 29% and sharps especially syringes are disposed up anyhow, although some form of incineration was reported (29%). Final disposal of the waste is often in open dumpsites. Training was reported, (64%) that generally focused more on personal safety rather than medical waste management. Infectious waste generated ranges from 0.07kg/day to 3.60kg/day, among public hospitals. Noninfectious waste generated ranges from 0.82kg/day to 1.6kg/day. Infectious wastes generated among private hospitals ranges from 0.22kg/day to 2.57kg/day while noninfectious waste generated ranges from 0.0kg/day to 1.10kg/day. Of the average total generated waste produced, 18.0kg/day, public hospitals accounted for about 11.8kg/day while private hospitals accounted for 6.20kg/day. The result indicated that the management of biomedical waste is poorly executed, hence it was recommended that strategic measures should take to reduce the quantity of the waste produced, which may be achieved full segregation of the wastes and implementation of National Health Care Waste Management Plan (NHCWMP, 2007) in order to reverse the situation.